Homelessness and health needs in Wales - Song, Jiao; Grey, Charlotte; Woodfine, Louise; Davies, Alisha (International Journal of Population Data Science, 2019)
Background Public Health Wales developed its long-term strategy with the purpose of ‘Working to Achieve a Healthier Future for Wales’. This study is motivated by one of the strategic priorities, ‘Influencing the wider determinants of health’ with an emphasis on homelessness prevention. Main Aim To understand health needs of homeless health service users from routinely collected health data in Wales. To quantify the corresponding differences from general population. Methods Scoping work has completed collaborating with academic researchers, third sectors, clinical professionals, Office for National Statistics, and housing stats of Welsh Government. To construct study cohort, we will perform linkage exercise among Annual District Death Extract, Emergency Department Data Set, Outpatient Dataset for Wales, Patient Episode Database for Wales, Substance Misuse Data Set and Welsh Longitudinal General Practice dataset (from 2007 to 2018) stored in Secure Anonymised Information Linkage (SAIL) Databank. Study cohort includes all patients with an indication (i.e. clinical codes) of homelessness in their registration information and/or health records. We propose to adapt propensity score matching to construct matched case and control groups. This method will assign each homeless individual to individual without homeless flag with same or similar propensity score. We will then proceed to test for the significance of the homelessness and each health and wellbeing indicators (i.e. physical health, mental wellbeing and substance misuse) in the presence of confounders, and estimate the effects of homelessness on these indicators. Results This study will demonstrate how linked data provide a more comprehensive review of the health needs of a vulnerable population, the homeless groups in Wales, and be able to explore changes over time. Conclusion The relationship between homelessness and health issues is bi-directional. Findings from this study will have implications for health, housing, social, and homelessness policy at both local and national level; as well as contributing to the ability to providing tailored health services to targeted homeless populations groups.